2021
DOI: 10.1128/aac.02489-20
|View full text |Cite
|
Sign up to set email alerts
|

Favipiravir and the Need for Early Ambulatory Treatment of COVID-19

Abstract: The commentary by McCullough emphasizes the urgent need for early ambulatory therapy of COVID-19 (1).…

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In part, based on a previously reported study, we postulated that favipiravir would improve clinical severity, patient quality of life, and COVID-19-related disease treatment burden in an ambulatory care setting. [15] Regarding the potential development of viral resistance, even though a previous study found scanty resistance by influenza virus to antivirals, [16] we suggest that physicians and policymakers adopt a cautious and well-considered approach when developing antiviral treatment policies. In this study, we found that more than half of patients with observable severe symptoms at the clinic registration date were unvaccinated and that there were higher proportions of partially and fully vaccinated patients in the nonsevere symptom group.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In part, based on a previously reported study, we postulated that favipiravir would improve clinical severity, patient quality of life, and COVID-19-related disease treatment burden in an ambulatory care setting. [15] Regarding the potential development of viral resistance, even though a previous study found scanty resistance by influenza virus to antivirals, [16] we suggest that physicians and policymakers adopt a cautious and well-considered approach when developing antiviral treatment policies. In this study, we found that more than half of patients with observable severe symptoms at the clinic registration date were unvaccinated and that there were higher proportions of partially and fully vaccinated patients in the nonsevere symptom group.…”
Section: Discussionmentioning
confidence: 79%
“…In part, based on a previously reported study, we postulated that favipiravir would improve clinical severity, patient quality of life, and COVID-19-related disease treatment burden in an ambulatory care setting. [ 15 ] Regarding the potential development of viral resistance, even though a previous study found scanty resistance by influenza virus to antivirals, [ 16 ] we suggest that physicians and policymakers adopt a cautious and well-considered approach when developing antiviral treatment policies.…”
Section: Discussionmentioning
confidence: 89%